Comparative genomics and transcriptomic response to root exudates of six rice root-associated Burkholderia sensu lato species - Wallner, Adrian; Klonowska, Agnieszka; Guigard, Ludivine; King, Eoghan; Rimbault, Isabelle; Ngonkeu, Eddy; Nguyen, Phuong; Béna, Gilles; Moulin, Lionel (Peer Community Journal)

(untitled)
Beyond being a reliable nutrient provider, some bacteria will perceive the plant as a potential host and undertake root colonization leading to mutualistic or parasitic interactions. Bacteria of the Burkholderia and Paraburkholderia genera are frequently found in the rhizosphere of rice. While the latter are often described as plant growth promoting species, Burkholderia are often studied for their human opportunistic traits. Here, we used root exudate stimulation on three Burkholderia and three Paraburkholderia strains isolated from rice roots to characterize their preliminary adaptation to the rice host at the transcriptomic level. Instead of the awaited genus-dependent adaptation, we observed a strongly species-specific response for all tested strains. While all bacteria originate from the rice environment, there are great disparities in their levels of adaptation following the sensing of root exudates. We further report the shared major functions that were differentially regulated in this early step of bacterial adaptation to plant colonization, including amino acids and putrescine metabolism, the Entner-Doudoroff (ED) pathway as well as cyclic diguanylate monophosphate (c-di-GMP) cycling.